Evaluating Specification Tests in the Context of Value-Added Estimation - Cassandra Guarino; Mark D. Reckase; Brian Stacy; Jeffrey M. Wooldridge (Institute for the Study of Labor (IZA), 2014)
We study the properties of two specification tests that have been applied to a variety of estimators in the context of value-added measures (VAMs) of teacher and school quality: the Hausman test for choosing between random and fixed effects and a test for feedback (sometimes called a falsification test). We discuss theoretical properties of the tests to serve as background. An extensive simulation study provides important further insight to the VAM setting. Unfortunately, while both the Hausman and feedback tests have good power for detecting the kinds of nonrandom assignment that can invalidate VAM estimates, they also reject in situations where estimated VAMs perform very well. Consequently, the tests must be used with caution when student tracking is used to form classrooms.
Keywords: C01; I20; J45; J01; 330; teacher labor markets; teacher quality; value-added